Countering Transnational Crime and Corruption: The Urge to Action Versus the Patience to Evaluate. (24th May 2018) - Albanese, Jay S.
Abstract: Dramatic moves have occurred in countering transnational crime since the turn of the twenty-first century. Binding international agreements, such as the UN Convention against Transnational Organized Crime, and the Convention against Corruption, are examples of nearly universally adopted principles and mandates that were difficult to foresee a generation ago. What is less clear is the extent to which these moves indicate true progress, versus actions and efforts that will ultimately be ineffective. This paper assesses significant changes over the last 20 years in responding to transnational organized crime, corruption and global injustice, and points to several efforts to evaluate their effectiveness. Specific content areas are identified in which ongoing evaluation is needed at the intersection between the urge to take action and the patience to evaluate.